Konsep Kebebasan Manusia menurut Wahbah Az-Zuhaili dalam Tafsir al-Munir: Kajian terhadap Humanisme Barat - Mochamad Hanif Ibnu Jatnika; Muhammad Rif'at Syauqi Syauqi (Mustaneer : Journal of Islamic Thought and Civilization, 2025)
The issue of human freedom is a significant topic in contemporary discourse, particularly in the intersection between Western values and Islamic teachings. This study aims to examine the concept of human freedom according to Wahbah az-Zuhaili in Tafsir al-Munir and to evaluate its relevance to Western humanist thought, which emphasizes absolute individual liberty. Using a qualitative method with a library research approach, data were obtained from Tafsir al-Munir as the primary source and Western philosophical literature as secondary sources. The findings reveal that Wahbah offers a balanced concept of freedom, acknowledging the human capacity to choose while limiting it within the framework of moral responsibility and divine law. Analysis of verses such as QS. Al-Kahfi [18]:29, QS. Al-Baqarah [2]:256, and QS. An-Najm [53]:39 demonstrates that Islam views freedom as a means toward conscious submission to the truth, rather than liberation from God’s laws. The novelty of this study lies in its comprehensive comparison between contemporary Islamic exegesis and secular humanism, producing an alternative framework to address the modern crisis of freedom. The implication is that this study affirms Islam’s position as a source of values capable of guiding human freedom ethically, spiritually, and socially in facing global challenges.